Three Dimensions of College Students’ Ecological Happiness View Education - Huang, Tian (Journal of Theory and Practice of Contemporary Education, 2023)
Ecological view of happiness education is an important project to cultivate college students' correct view of happiness. Based on the dimension of demand theory, the ecology of college students happiness concept education meets the needs of self, society and country development; Based on the epistemological dimension, the ecological happiness concept education of college students is powerful in today's society, some students ignore ecology, dissimilation ecological view and other wrong understanding; Based on the practical dimension, college students are lucky.With the characteristics of times, innovation and pleasure, blessing education promotes the continuous production of individual ecological behavior. Develop the ecological happiness view of college students .Education is conducive to the all-round development of college students, but also for the construction of socialist ecological civilization with Chinese characteristics to train reserves and successors.